Ultrafine Pd@PdPt nanowires with a single-atom alloy shell for efficient formate oxidation. Issue 46 (22nd November 2022) - Jiang, Yu-Chuan; Ding, Yu; Li, Fu-Min; Yin, Shi-Bin; Li, Dong-Sheng; Li, Xi-Fei; Chen, Yu
Abstract : Ultrafine Pd@PdPt nanowires with a Pd–Pt single atom alloy shell achieve significantly enhanced electrocatalytic performance towards the formate oxidation reaction. Abstract : The intrinsically sluggish kinetics of Pt towards the formate oxidation reaction (FOR) severely impedes its application in direct formate fuel cells (DFFCs). This study reports the synthesis of ultrafine Pd@PdPt nanowires (NWs) with a Pd–Pt single-atom alloy shell via an atomic galvanic displacement reaction. Pd@PdPt0.024 NWs with optimized composition exhibit a remarkable promoted specific activity of 98.2 A m −2 at 0.59 V towards the FOR, which is a 6.5- and 117.7-fold activity enhancement compared to original Pd NWs and commercial Pt catalysts. Density functional theory (DFT) calculations reveal that the electronic interaction between Pd and Pt as well as the modified Pt coordination environment endow the atomically dispersed Pt active site with an altered d-band structure and unique adsorption properties with a broken scaling relationship. The development of Pd@PdPt0.024 NWs will stimulate deeper insight into the FOR mechanism on Pt and hold promise for practical applications in DFFCs.